2023
DOI: 10.36660/abc.20220819
|View full text |Cite
|
Sign up to set email alerts
|

A Relação entre a Relação Ácido Úrico/Albumina e a Espessura Média-Intimal da Carótida em Pacientes com Hipertensão

Abstract: Fundamento: A hipertensão causa inflamação subendotelial e disfunção na aterosclerose resultante. A espessura médiaintimal da carótida (EMIC) é um marcador útil de disfunção endotelial e aterosclerose. A razão ácido úrico/albumina (RUA) emergiu como um novo marcador para prever eventos cardiovasculares. Objetivo: Nosso objetivo foi investigar a associação da RUA com a EIMC em pacientes hipertensos. Método: Duzentos e dezesseis pacientes hipertensos consecutivos foram incluídos neste estudo prospectivo. Todos o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
(93 reference statements)
0
2
0
2
Order By: Relevance
“…As evidenced in the methodology, patients with congestive heart failure, secondary hypertension, moderate to severe valvular heart disease, coronary artery disease, chronic kidney or liver disease, malignancy, active infection, and chronic inflammatory disease, in addition to those taking medications that affect serum levels of uric acid and/or albumin and those with malnutrition. 1 However, we observed that individuals affected by peripheral arterial obstructive disease were not included in the research exclusion criteria, which may confuse the results presented since the evidence regarding the correlation between atherosclerotic deterioration of the arterial wall in peripheral vascular territories and the increase in CIMT, have already been demonstrated for some decades. 7 It is, therefore, necessary to consider this comorbidity among the exclusion criteria for a better analysis of the results obtained in the study.…”
mentioning
confidence: 87%
See 3 more Smart Citations
“…As evidenced in the methodology, patients with congestive heart failure, secondary hypertension, moderate to severe valvular heart disease, coronary artery disease, chronic kidney or liver disease, malignancy, active infection, and chronic inflammatory disease, in addition to those taking medications that affect serum levels of uric acid and/or albumin and those with malnutrition. 1 However, we observed that individuals affected by peripheral arterial obstructive disease were not included in the research exclusion criteria, which may confuse the results presented since the evidence regarding the correlation between atherosclerotic deterioration of the arterial wall in peripheral vascular territories and the increase in CIMT, have already been demonstrated for some decades. 7 It is, therefore, necessary to consider this comorbidity among the exclusion criteria for a better analysis of the results obtained in the study.…”
mentioning
confidence: 87%
“…Lemos, atentamente, o artigo intitulado: "A relação entre a razão ácido úrico/albumina e a espessura média-intimal da carótida em pacientes com hipertensão" , cujo objetivo foi investigar a associação da relação ácido úrico/albumina (RUA) e a espessura média-intimal carotídea (EMIC) em pacientes hipertensos. 1 Embora o presente estudo tenha demonstrado uma correlação significativa entre RUA e EMIC, com a RUA apresentando maior capacidade discriminativa para valores aumentados de EMIC do que ácido úrico e albumina isolados, e do que os demais marcadores inflamatórios analisados no estudo, como o índice de inflamação imune sistêmica (IIS), a razão neutrófilo/linfócito (RNL), a razão plaqueta/linfócito (RPL) e a razão proteína C reativa/albumina (RCA), 1 alguns aspectos observados, na leitura do artigo, são dignos de nota.…”
unclassified
See 2 more Smart Citations